Chapter L'interazione tra la diatesi Non-attiva e le categorie di tempo e aspetto. Microvariazione nei dialetti italo-albanesi - TURANO, Giuseppina (Biblioteca di Studi Slavistici, 2023)
This article deals with morphological non-active verbal voice, which characterises reflexive, middle and passive structures in Standard Albanian and Arbëresh dialects. The data, compared to those of Italian, show that the three different strategies for the realisation of Standard Albanian and Arbëresh non-active morphology interact with the categories of mood, tense and aspect. In particular, these morphological strategies determine a perfective/ imperfective split as well as a series of restrictions which convey different interpretations associated with a stative or eventive interpretation. Particular attention is paid to the possible influence of Italian structures on the Italo-Albanian varieties in the domain of non-active voice.